Application of Audio Visual Learning Media to Improve Learning Outcomes of Nutritious Eating Materials in Grade VIII F SMPN 8 Banjarbaru Students - Azizah, Rahma; Rakhman, Arie; Putra, Trinaldi Andika (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This research against the background of low student learning outcomes on nutritious food materials shows the need to implement more interesting and meaningful learning strategies. Although audio-visual media has been widely used in learning, classroom action research examining its use in nutritious food materials by integrating problem-based LKPD, group discussions, and collaborative learning activities is still limited. This study aims to describe the improvement of student learning outcomes through the application of learning that utilizes audio-visual media on nutritious food materials. This study uses the Classroom Action Research (PTK) method which is carried out in two cycles with 25 research subjects in class VIII F SMP Negeri 8 Banjarbaru. Data was collected through learning outcome tests, observation sheets of learning activities, and learning motivation questionnaires. The data was analyzed in a quantitative descriptive manner by calculating the percentage of learning completeness, learning activities, and learning motivation of students in each cycle. The results showed that the learning completion percentage increased from 40% in the pre-cycle, to 68% in the first cycle, and 88% in the second cycle. The average grade point of the class also increased from 71 pre-cycle, to 76 in cycle I and 80 in cycle II. Students' learning activities have increased, which is marked by an increase in the percentage of students in the good and excellent categories from 20% in the pre-cycle to 48% in Cycle I and 80% in Cycle II. Learning motivation as supporting data also increased from 38.00% in pre-cycle to 56.00% in Cycle I and 71.33% in Cycle II.The findings of the study indicate that the use of audio-visual media supported by problem-based LKPD, group discussions, interactive quizzes, and teacher assistance during the learning process contributes to improving students' learning outcomes, motivation, and learning activities on nutritious food materials.